KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 7 PADANG - Khairun Nisa; Nursaid Nursaid (Universitas Negeri Padang, 2020)
ABSTRACTThis study revealed the contribution of reading comprehension skills toward writing skill related to the description texts of that made by grade VII students of SMP Negeri 7 Padang. The purpose of this study was categorized into three-part. First, to describe the writing skills of the description text of grade VII students of SMP Negeri 7 Padang. Second, to describe the reading skills of students in grade VII of SMP Negeri 7 Padang.. Third, to describe the contribution of reading comprehension skill to the writing skill of the description texts of grade VII students of SMP Negeri 7 Padang. This type of study was quantitative with descriptive methods. The design used in this study was the contribution design. The population of this study was students of class VII SMP Negeri 7 Padang in the 2018/2019 academic year about 251 students. The sample in this study was determined by proportional random sampling 15% of the population that was 40 students. The data of this study were in the form of scores on reading comprehension skill test scores and scores on writing description text skill. The data were obtained through two types of tests namely objective tests to measure the comprehension of reading skill and performance tests to measure description text writing skill. There were three results of this study. First, the description writing skill of grade VII students of SMP Negeri 7 Padang was in good qualifications (B) with an average of 76.80. Second, reading comprehension skill of grade VII students of SMP Negeri 7 Padang was in good qualifications (B) with an average of 82.50. Third, there was a contribution to reading comprehension text skill on the ability to write description texts of grade VII students of SMP Negeri 7 Padang with percentage 42, 51%. Kata kunci: Kontribusi, Keterampilan, Membaca Pemahaman, Menulis, Teks Deskripsi